Alliance entrepreneurship and entrepreneurial orientation: the mediating effect of knowledge transfer - Arash Rezazadeh; Mahsa Mahjoub (Gadjah Mada International Journal of Business, 2016)
Today’s rapidly changing business environment has impelled companies to cooperate with their competitors gaining more competitive advantages by achieving win-win situation. Thereby, building alliances as one of the cooperative strategies has been adopted by many enterprises, consequently attracting great attention of numerous scholars. Nevertheless, the alliance literature seems to lack studies in the domain of entrepreneurship. Accordingly, this paper aims to extend entrepreneurship into the field of alliances highlighting two phenomenal concepts: alliance entrepreneurship and entrepreneurial orientation. Hence, the relationship between these two constructs together with the mediating role of knowledge transfer between alliance partners are investigated. We used Structural Equation Modeling with Partial Least Squares (PLS-SEM) technique under two sections of measurement model and structural model assessment in order to analyze data. The results gathered from Iran’s automotive industry confirmed the positive significant impact of alliance entrepreneurship on partners’ entrepreneurial orientation and the mediating effect of knowledge transfer